POLITIK KRIMINAL PENANGGULANGAN TINDAK PIDANA KEKERASAN PSIKIS TERHADAP ANAK DALAM RUMAH TANGGA - Aji Lukman Ibrahim (Arena Hukum, 2022)
This study aims to find the prime causes of psychological violence against children in the household and to formulate policies to overcome psychological violence against children in the household. This normative research uses a statute approach and a conceptual approach. The results of the study indicate that there are several prime causes of psychological violence in the household, such as the perpetrator’s lack of knowledge about the forms of domestic violence, the closure of children as victims, less harmonious relationships among family members, wrong way of parenting, psychological factors of the perpetrator, economic factors and the Covid-19 Pandemic. Overcoming psychological violence against children in the household can be done with a single-track system (penal) in the form of conditional sentence which is applied as shock therapy in order to prevent the perpetrator from repeating his actions. The double track system is in the form of action against the perpetrator, namely consultation with a psychologist. Meanwhile, non-penal efforts are in the form of pre-marital debriefing to the bride and groom about the forms of domestic violence, children’s rights and good parenting.